PENERAPAN METODE DEMONSTRASI UNTUK MENINGKATKAN KEAKTIFAN DAN PRESTASI BELAJAR - Tenang Helen Pandika (UNIB Press, 2022)
This study aims to increase student activeness and learning achievement in Chemistry class XI MIPA SMA N 2 Pagar Alam by applying the demonstration method. The type of research used is Classroom Action Research (PTK), and quasy experiment. This classroom action research was conducted in 3 cycles, each of which consisted of planning, implementing, observing and reflecting. The subjects of this study of class XI MIPA 1, amounting in the XI MIPA 2 experiment class, and in kontrol the XI MIPA 3 class. Collecting data using observations and student test results sheets. The data analysis used mean and t-test. The results of this study can be concluded that the use of demonstration methods can increase student activeness and learning achievement in Chemistry class XI MIPA SMA N 2 Pagar Alam.